SPECTRUM OF ANEMIA IN ADOLESCENTS ADMITTED AT A TERTIARY CARE CENTRE: A RETROLECTIVE STUDY - NEHA NATHE; Vidya Kale; Mamata Havnur; Kunal Torane; Dr Bharati Deore (Tropical Journal of Pathology and Microbiology, 2024)
Introduction: Anemia in adolescents needs to be studied as it affects the development and health of an individual in adult life. Adolescent anemia refer to a group of anemias that occur in the age between 10- 19 yrs. Anemia in adolescents needs to be studied as it affects the development and health of an individual in adult life. Morphological examination of anemia is important to find out underlying cause.Material and Methods: A Retrospective Observational study conducted on patients of 10- 19 years old visiting hematology section of central clinical laboratory at Dr VPMCH and RC Nashik, Maharashtra from September 2022 to September 2023.Results: Total 473 patients were included in the study of which 323(68% were anemic. This includes 54% females and maximum patients were in late adolescence stage. On studying RBC Indices and morphology, it was observed that 242(75% cases had Microcytic Hypochromic anemiaConclusion: Anemia is most commonly seen adolescents especially in girls of late adolescent age group. Microcytic hypochromic Anemia is most common among adolescents. Morphological assessment is necessary in all cases for accurate diagnosis and treatment.